2022
DOI: 10.1186/s12944-022-01741-8
|View full text |Cite|
|
Sign up to set email alerts
|

The blood monocyte to high density lipoprotein cholesterol ratio (MHR) is a possible marker of carotid artery plaque

Abstract: Background MHR is the ratio of monocyte to high-density lipoprotein cholesterol (HDL-C). It has been reported that MHR changes are associated with cardiovascular and cerebrovascular disease. Carotid plaque is a common vascular lesion of the carotid artery and is a manifestation of atherogenesis. This study investigated the relationships between the MHR and the incidence of carotid plaques. Methods The data of 3848 physical examiners were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(40 reference statements)
0
13
0
1
Order By: Relevance
“…Previous studies have evaluated the association between the monocyte-to-HDL-C ratio and cardiovascular mortality, 27 diabetic retinopathy, 28 and carotid plaque. 29 However, the relationship between the monocyte-to-HDL-C ratio and BMD has not been reported. The current study found that the monocyte-to-HDL-C ratio was mainly associated with BMD and osteoporosis in females.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the association between the monocyte-to-HDL-C ratio and cardiovascular mortality, 27 diabetic retinopathy, 28 and carotid plaque. 29 However, the relationship between the monocyte-to-HDL-C ratio and BMD has not been reported. The current study found that the monocyte-to-HDL-C ratio was mainly associated with BMD and osteoporosis in females.…”
Section: Discussionmentioning
confidence: 99%
“…showing that MHR levels increase as carotid plaque severity increases in those without hypertension or diabetes (11). Data related to MHR in stroke have been interpreted mostly on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…formation and can be used as a possible marker for plaque formation and severity may be relevant in this regard (11).…”
Section: Introductionmentioning
confidence: 99%
“…A study about the involvement of the Monocytes/HDL-C ratio as a biomarker in carotid artery plaque formation found that the Monocytes/HDL-C ratio positively correlated with body mass index (BMI) as a hallmark in diagnosing obesity and Hb1Ac, therefore representing potential links between T2DM and MetS ( 21 ).…”
Section: Discussionmentioning
confidence: 99%